2016
DOI: 10.1002/anie.201605571
|View full text |Cite
|
Sign up to set email alerts
|

A Molybdenum(0) Isocyanide Analogue of Ru(2,2′‐Bipyridine)32+: A Strong Reductant for Photoredox Catalysis

Abstract: We report the first homoleptic Mo(0) complex with bidentate isocyanide ligands, which exhibits metal-to-ligand charge transfer ((3) MLCT) luminescence with quantum yields and lifetimes similar to Ru(bpy)3 (2+) (bpy=2,2'-bipyridine). This Mo(0) complex is a very strong photoreductant, which manifests in its capability to reduce acetophenone with essentially diffusion-limited kinetics as shown by time-resolved laser spectroscopy. The application potential of this complex for photoredox catalysis was demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
171
1
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(182 citation statements)
references
References 97 publications
8
171
1
2
Order By: Relevance
“…[1,2] Except for copper(I) complexes, [2] strongly luminescent molecular complexes of earth-abundant-metal ions were essentially unknown until very recently.N ear-IR (NIR) emission with mononuclear copper(I) complexes is still very rare. [4][5][6][7][8] Milsmann and co-workers reported aluminescent zirconium-(IV) complex bearing 2,6-bis(pyrrolyl)pyridine ligands. [3] Ah andful of examples of luminescent complexes based on earth-abundant-metal ions with d n electron configuration (n < 10) only became available in the last three years (Scheme 1).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…[1,2] Except for copper(I) complexes, [2] strongly luminescent molecular complexes of earth-abundant-metal ions were essentially unknown until very recently.N ear-IR (NIR) emission with mononuclear copper(I) complexes is still very rare. [4][5][6][7][8] Milsmann and co-workers reported aluminescent zirconium-(IV) complex bearing 2,6-bis(pyrrolyl)pyridine ligands. [3] Ah andful of examples of luminescent complexes based on earth-abundant-metal ions with d n electron configuration (n < 10) only became available in the last three years (Scheme 1).…”
mentioning
confidence: 99%
“…They include ligand-to-metal charge transfer (LMCT), metal-to-ligand (MLCT), and spin-flip emitters. [6,7] Thec hromium(III) complex [Cr(ddpd) 2 ] 3+ (1 3+ ) [8] with ad 3 electron configuration is based on the tridentate strongfield ligand N,N'-dimethyl-N,N'-dipyridine-2-yl-pyridine-2,6diamine (ddpd) introduced into coordination chemistry by the Heinze group (Scheme 1). [4] A unique low-spin hexacarbene iron(III) complex with LMCT emission has been reported by Wärnmark.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[4] Some fruitful approaches to destabilize the energy of the 3 MC states consist of a) introduction of strong donor ligands and b) the use of tridentate ligands that form 6-membered chelate rings to reduce the steric strain and achieve am ore octahedral geometry compared to those bearing five-membered chelate rings. Recently,W enger and Gray et al observed 3 MLCT emission of earth abundant low-valent Cr 0 , [13] Mo 0 , [14] and W 0 [15] complexes with arylisocyanide ligands. Recently,W enger and Gray et al observed 3 MLCT emission of earth abundant low-valent Cr 0 , [13] Mo 0 , [14] and W 0 [15] complexes with arylisocyanide ligands.…”
mentioning
confidence: 99%